Frontal crash seat belt restraint effectiveness and comfort accessories used by older occupants. (2nd January 2020) - Whyte, Tom; Kent, Nicholas; Keay, Lisa; Coxon, Kristy; Brown, Julie
Abstract: Objective: Around a quarter of older occupants use some type of comfort or orthopedic aftermarket accessory on the vehicle seat while traveling in a vehicle. The aim of this study was to investigate the effect of comfort accessories on the performance of the seat belt restraint system in a frontal crash in terms of potential injury implications for older occupants. Methods: Eight frontal sled tests (43 km/h, 32 g ) were carried out on a deceleration sled fitted with a three-point lap-sash seat belt and a front passenger seat from a common Australian passenger car for each test. A 5 th percentile Hybrid III anthropometric test device (ATD) was positioned in the seat and measurements were recorded for head center of gravity acceleration, chest acceleration, neck forces and moments and sternal deflection. Tests were carried out in a baseline condition and with seven comfort accessories. Each comfort accessory was inserted between the ATD and vehicle seat as it is intended to be used, with the ATD otherwise positioned as close as possible to the baseline test position. Results: Initial distance between the seat belt anchor and ATD hip was associated with a statistically significant decrease in Head Injury Criterion and increase in sternal deflection. Submarining was related to the ATD torso recline angle and angle of the lap belt from the seat belt anchor. Conclusions: Accessories placed between the seat back and the lumbar region of an occupant have the potential to increase the risk of submarining due to a change in posture and should be avoided if such a change in posture when seated with an accessory is excessive. Sitting on seat cushions resulted in the greatest increase in seat belt anchor to hip distances and hence largest increase in sternal deflection. Given the fragility, frailty and particular importance of chest injuries among older vehicle occupants, further investigation is needed to determine whether these changes in ATD sternal deflection observed with seat cushion use results in injury threshold limits being exceeded and whether pretensioners and load limiters would ameliorate these effects without causing other negative changes in occupant response or kinematics.